Breeding phenology of Bufo viridis Laurenti, 1768 in Sicily - Alessandra Sicilia; Francesco Lillo; Bruno Zava; Franco Bernini (Acta Herpetologica, 2007)
Bufo viridis Laurenti, 1768 is a common species that inhabits a wide variety of habitats. The different climates characterising its broad range lead to a high degree of variability in its seasonal activity and reproductive cycle. This paper reports some observations carried out on the breeding phenology of this species over a two year period in Mediterranean temporary ponds in Sicily. The reproductive period of Sicilian green toads extends into the autumn months, making it longer than that of other Italian populations. This behaviour seems due to the impact of xeric environmental conditions on the seasonal activity of the studied populations. The present study confirms that B. viridis is an opportunistic breeder with a wide margin of variability in annual reproductive cycle patterns, as would be expected of an ecologically variable species. The duration of the reproductive season varied between populations in the same year and between different years for the same population.